Reduction of emissions by avoided deforestation in andean high-land tropical forests - Andrade, Hernán J.; Segura, Milena A.; Escobar, Erika A. (Revista de Ciencias Agrícolas, 2021)
Deforestation and forest degradation, mainly in areas with high carbon density, is one of the most important source of greenhouse gases (GHG). The impact of deforestation on carbon storage in total biomass and its CO2 emissions is analyzed in four land covers in the Santuario de Fauna y Flora Iguaque (SFFI), Boyacá, Colombia. A total of 32 temporal sampling plots (TSP) of 250m2 was established to measure trees with diameter at breast height (dbh) ³ 10 cm whereas 17 TSP of 36m2 were established to measure total and stipe height of all frailejones (Espeletia boyacensis Cuatrec, E. tunjana Cuatrec and E. cf. Incana). Above and belowground biomass was estimated with allometric models, whereas carbon was calculated using the 0.47 fraction. The sampling area was proportional to the area of each land cover: open heathlands and moorlands (OMH), dense heathlands and moorlands (DMH), broad-leaved forest with continuous canopy, not on mire (BFCC), natural grassland prevailingly without trees and shrubs (NSWT). BFCC and DMH showed higher carbon storage in biomass (55 and 27Mg C/ha, respectively). SFFI stored around 135.9Gg C, from which 25-38Gg CO2e could be emitted to the atmosphere in the 20 next years if the deforestation rates continue. BFCC and OMH are the covers with the highest potential of CO2 emissions to the atmosphere. Therefore, prioritizing the preservation of these ecosystems by Reducing Emissions from Deforestation and Degradation (REDD+) programs, is a key to counter the effects of climate change and ensure the supply of ecosystemic services that support local communities’ livelihoods.